DEVELOPMENT OF READY TO BAKE PLANT BASED CAKE MIXTURE FOR VEGETARIANS AND EGG ALLERGENS - Aberathne, P.K.G.M.P.; Navaratne, S.B.; Wickramasinghe, I. (Tropical Agricultural Research & Extension, 2016)
Attached

A ready to bake cake mixture was developed using Wheat, Sugar, coconut milk powder, baking powder, corn starch, xanthan gum, vanilla flavour and clean! of larlar. Combination of corn starch, baking powder and xanthan gum were used as egg substitution. I ight samples were prepared and the best treatment was selected in terms of sensory properties. Proximate anti shell' life analysis were carried out for (he best treatment. The best treatment was organoleptically compared with vaiiilla flav oured cake. Results revealed that there was no significant difference between the two prfidhef’ in Overall acceptability. Proximate analysis revealed that developed cake mixture having lower amount of protein and fal Ilian (lie normal cake due to absence of egg and butter. Coconut milk powder was the only fat source which contributes around 16.74% Tat into the final product. The shelf life analysis for the final product was carried old lot Iwo months by testing the sensory attributes, moisture content, peroxide value and microbial count under trto fvpes of packaging materials ( Triple laminated and Polypropylene) as well as at two different temperatures ll"< ( Ambient) and 4"( (Refrigerated). The sensory attributes along with microbiological level, moisture content and peroxides value of the sample packed in Polypropylene and kept under ambient temperature only had ii significant deviation at the end of two months shelf life
Keywords: coconut milk powder; corn starch; cream of tartar; Polypropylene; Triple laminated and Xanthan gum